Developing students' English vocabulary through translation activities using narrative text - Syamsia, S; La Jie, Erisa (Jurnal Langua, 2024)
The objective of this research was to determine whether translating narrative texts could enhance students' English vocabulary. The study identified that students struggled with English largely due to limited vocabulary, which hindered their ability to form responses and led to frustration and hesitation. Despite ongoing efforts, teachers had not effectively addressed this issue or engaged students in meaningful, interactive activities. To address this, the researchers implemented translation activities involving narrative texts to improve vocabulary acquisition. This qualitative descriptive study involved 20 eighth-grade students from SMP Negeri 47 Halmahera Selatan, out of a population of 98. Data were collected through tests, observations, and interviews, and analyzed using data reduction, display, and conclusion-drawing techniques. Results showed that 13 of the 20 students scored above average. Specifically, 2 students achieved perfect scores, 5 received good scores, 6 obtained satisfactory scores, and 7 scored below average. The study found that using narrative text translation activities to develop students' vocabulary was effective, achieving a 65% improvement rate.